2011
DOI: 10.1038/ijo.2011.97
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of olanzapine on ghrelin secretion, CCK sensitivity, meal size, locomotor activity and body temperature

Abstract: Objective: Significant weight gain is a problematic side effect of treatment with the antipsychotic drug olanzapine (OLA). Previous studies in rats suggest that one of the contributing factors is an impairment in satiation that results in increased food intake. However, the mechanisms underlying this impairment in satiation remain largely unclear. Methods and results: In this study, we determined the effect of OLA on levels of leptin, insulin, ghrelin, cholecystokinin (CCK), glucagon-like peptide-1, peptide YY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…However, one short-term study suggested that eight days of olanzapine treatment can lead to small but significant increase in pre-and postprandial total ghrelin levels (Vidarsdottir et al, 2010), indicating an acute upregulatory effect of SGAs on ghrelin production. This view is supported by two pharmacological animal studies which showed that acute olanzapine or clozapine treatments can increase both preand postprandial total ghrelin levels in rodents (van der Zwaal et al, 2012). Furthermore, our preliminary data also showed that one week of oral olanzapine treatment can increase plasma total ghrelin levels in rats (Zhang et al, unpublished data).…”
Section: Initial Effects Of Sgas On Circulating Ghrelin Productionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, one short-term study suggested that eight days of olanzapine treatment can lead to small but significant increase in pre-and postprandial total ghrelin levels (Vidarsdottir et al, 2010), indicating an acute upregulatory effect of SGAs on ghrelin production. This view is supported by two pharmacological animal studies which showed that acute olanzapine or clozapine treatments can increase both preand postprandial total ghrelin levels in rodents (van der Zwaal et al, 2012). Furthermore, our preliminary data also showed that one week of oral olanzapine treatment can increase plasma total ghrelin levels in rats (Zhang et al, unpublished data).…”
Section: Initial Effects Of Sgas On Circulating Ghrelin Productionsupporting
confidence: 73%
“…Clinical data has indicated ghrelin production and signalling is upregulated, at least in a subpopulation of patients under SGA treatments (Esen-Danaci et al, 2008;Murashita et al, 2007a;Murashita et al, 2005;Palik et al, 2005;Perez-Iglesias et al, 2008), which was supported by the majority of acute and chronic animal studies (Murashita et al, 2007b;van der Zwaal et al, 2012;Weston-Green et al, 2011). Although ghrelin signalling is only indirectly related to SGAs, and therefore other mechanisms (for example, antagonism of H1, H3, 5-HT2a, M3 receptors) cannot be excluded, the majority of data as discussed above indicate that the altered ghrelin signalling under SGA treatments can at least partly explain the weight gain sideeffects induced by SGAs.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 96%
“…Consistent with this, there is significant incidence of somnolence in people treated with many second-generation APDs (Gao et al, 2008 ). Furthermore, thermogenesis is another measure of body energy consumption and olanzapine administration was shown to cause reductions in body core temperature in animal model (van der Zwaal et al, 2012 , 2014 ). Therefore, these drug-induced decreases in body core temperature suggest overall decreases in energy expenditure.…”
Section: Apd-induced Effects On Appetite and Energy Consumptionmentioning
confidence: 99%
“…Although a recent study found an increased heat production in mice treated with olanzapine (Lord et al, 2017 ), a previous study reported a decrease of metabolic rate in mice with olanzapine infusion (8 mg/kg/day) but not in mice with a lower dose (4 mg/kg/day) (Coccurello et al, 2009 ). Furthermore, a number of studies in rats reported that olanzapine reduced core body temperature or thermogenesis of brown adipose tissue (BAT) accompanied with decreased expression of functional thermogenic proteins, uncoupling protein1 (UCP1) and peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α) of BAT (Stefanidis et al, 2009 ; van der Zwaal et al, 2012 ; Zhang et al, 2014b ). Therefore, further studies are necessary to clarify the effects of APDs on thermogenesis.…”
Section: Mechanisms For Antipsychotic-induced Diabetesmentioning
confidence: 99%